TINDAK TUTUR ILOKUSI DALAM FILM RUDY HABIBIE - Mahardika, Gustianti; Mustafa, M. Nur; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, The purpose of this research (1) to describe illocutionary language acts in the film Rudy Habibie; (2) Describe how the delivery illocutionary speech acts in the movie Rudy Habibie. This type of research is descriptive research, ie solving existing problems based on existing data. Sources of data in this study are the pronunciation antartokoh in the film Rudy Habibie, which was released on June 30, 2016. The collection of data techniques in this study is the transcript of engineering techniques used to analyze data directly. Based on the analysis in this study, 137 found illocutionary language acts consisting of the form of illocutionary language acts assertive, directive, commissive, expressive and declarative. The details of this information (1) The form of illocutionary assertive language acts are 71 expressions; (2) the form of a directive illocutionary language sentences number 44; (3) form commissive illocutionary language expression was 6; (4) -form illocutionary speech deeds expressive speech was 7; And (5) a declarative illocutionary language act was 9 speech. In this study, two ways were found that illocutionary language use consists of delivering illocutionary speech direct and indirect actions. The submission of illocutionary language acts directly found 85, while the delivery of illocutionary language acts indirectly total 52 ways.Keywords: illocutionary speech act, pragmatis, and rudy habibie.